Can rs3767140 SNP of the perlecan (HSPG2) gene affect the diabetes mellitus through the dyslipidemia? - Kurnaz-Gömleksiz, í–; Tokat, B; Aslan, E I; Yanar, F; Ermiş-Karaali, Z; í–ztürk, O; Yilmaz-Aydoğan, H (Cellular and Molecular Biology, 2016)
Perlecan (HSPG2) play an important role in the lipoprotein metabolisms. The G allele of the HSPG2-rs3767140 may affect the binding of heparan sulfate (HS) chains and hence cause loss of HS from the basement membrane. HSPG2-rs3767140 was studied in 60 T2DM patients and 109 healthy controls. In diabetic patients HSPG2-rs3767140 T variant allele carriers (TT+GT) have decreased fasting plasma glucose (FPG) and serum LDL-C levels (p=0.071 and p=0.060, respectively) versus GG genotype carriers. Moreover, in both of the two groups in which the T allele carriers HDL-cholesterol levels tend to be high. We investigated that the HSPG2-rs3767140 promoted to the dyslipidemic phenotype in the type 2 diabetes mellitus (T2DM) patients. We suggest that the HSPG2-rs3767140 might be associated with the decreased FPG and LDL-C and with the increased HDL-C in diabetics. Therefore, the HSPG2-rs3767140 might be a protective for the diabetes mellitus due to its ameliorating effect on the dyslipidemic phenotype.